Does a Staged Posterior Approach Have a Negative Effect on OTA 43C Fracture Outcomes?. Issue 2 (February 2017) - Chan, Daniel S.; Balthrop, Paul M.; White, Brian; Glassman, David; Sanders, Roy W.
Abstract : Objective: To determine whether multiple approaches pose an increased risk to fracture healing when compared with a standard single approach in the treatment of pilon (OTA 43C) fractures. Design: Retrospective review of a prospective database. Setting: Level I academic trauma center and level II community trauma center. Methods: From January 1, 2005 to December 31, 2011, all records of patients treated for OTA 43C fractures of the distal tibia were reviewed. Patients were grouped according to multiple (posterior-anterior) and single (anterior-alone) approaches. Medical charts and surgical documentation were reviewed and postoperative computed tomography (CT) scans were examined for residual articular displacement and quantified. Ultimate union rate was correlated with approach strategy. Articular reduction was subdivided into 3 groups (<1, 1–2, and >2 mm). Results: A total of 116 patients were identified as having had 43C fractures treated surgically with postoperative CT scans completed. Twenty-six fractures presented as an open injury. Of these 116 patients, 35 underwent staged fixation of the posterior malleolar component at an average of 2 days postinjury, followed by delayed anterior fixation at an average of 14 days postinjury. The remaining 81 patients underwent anterior fixation alone, on average 17 days postinjury. Twenty-one patients were lost to follow-up before 12 months. Of the 95 patients with sufficient follow-up (≥12 months), there were 24 nonunions. There was a statistically significant association of nonunion with staged posterior approach (40% vs. 19%, P = 0.015). CT reduction for staged posterior versus anterior-alone approach was not significantly different for any of the 3 categories (63% vs. 57% <1 mm, 31% vs. 26% 1–2 mm, and 6% vs. 17% >2 mm). Conclusions: In this series, there was no statistically proven benefit to combined surgical approaches to tibial pilon fractures with regard to the quality of articular reduction. It appears from this investigation that there may be a significantly higher risk of nonunion associated with the addition of the staged posterior approach. Although articular reduction is of paramount importance, multiple approaches for direct reduction and fixation of all fragments may lead to further complications. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.